Stearic acid / chitosan modified multiwalled carbon nanotube modified waterborne epoxy resin as well as preparation method and application thereof

Modify the multi -wall carbon nanopotransorbitarized water -based epoxy resin through lipidic acid/shell polysaccharis, solve the problem of poor tightness and rapid failure of coating, and realize the high density and corrosion resistance of the coating.

CN119350801AActive Publication Date: 2025-01-24ANHUI UNIV

Patent Information

Application Number
CN202411264993.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-24
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

The aqueous epoxy resin coating is prone to micropores and microcracks during the curing process, resulting in poor density and rapid failure of the coating. Due to chemical inertia and agglomeration, multi-walled carbon nanotubes affect their enhancement effect in composite materials.

Method used

Modify multi-walled carbon nanotubes with stearic acid/chitosan and modify water-based epoxy resin to increase cross-linking density and reduce surface energy, enhance interface bonding strength, reduce microporous defects, and improve the hydrophobicity and shielding properties of the coating .

Benefits of technology

It significantly improves the density and corrosion resistance of the coating, delay the adsorption and entry of the corrosive media, and significantly enhance the shielding performance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350801A_ABST
    Figure CN119350801A_ABST
Patent Text Reader

Abstract

The invention discloses stearic acid / chitosan modified multi-walled carbon nanotube modified waterborne epoxy resin and a preparation method and application thereof, and relates to the technical field of anticorrosive paints.The preparation method comprises the steps that chitosan is adsorbed and wrapped on the surface of a multi-walled carbon nanotube through a surface deposition cross-linking method to improve the dispersity of the multi-walled carbon nanotube; then stearic acid is grafted through a water-soluble coupling agent to synthesize a stearic acid / chitosan modified multi-walled carbon nanotube, and the stearic acid / chitosan modified multi-walled carbon nanotube is added into water-borne epoxy resin, so that the crosslinking density of the epoxy resin can be effectively improved, the surface energy of an epoxy resin coating can be reduced, and the contact area of a hydrophobic surface and a corrosive medium is reduced; adsorption of corrosive media is effectively prevented, and the time that the corrosive media enter the coating is delayed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anti-corrosion coatings, and in particular to a stearic acid / chitosan modified multi-walled carbon nanotube modified waterborne epoxy resin and a preparation method and application thereof. Background Art

[0002] People use a lot of metal materials in daily production, and water-based epoxy resin anti-corrosion coating is an effective anti-corrosion coating. However, the condensation and cross-linking of organic molecules in the curing process of water-based epoxy resin coating will affect the density of the coating, resulting in a large number of micropores, microcracks and other defects. These defects will become diffusion channels for corrosive ions, thus causing the coating to fail quickly.

[0003] Multi-walled carbon nanotubes (MWCNTs) have attracted attention for enhancing the mechanical and corrosion properties of polymer coatings due to their excellent chemical resistance, ultra-high aspect ratio, and mechanical stability. However, MWCNTs exhibit chemical inertness and aggregate in solutions and coating matrices within a short period of time through π-π interactions and van der Waals forces, which affects the reinforcing effect of MWCNTs in composites. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a preparation method of stearic acid / chitosan modified multi-walled carbon nanotube modified water-based epoxy resin. The epoxy resin is modified by stearic acid / chitosan modified multi-walled carbon nanotubes, which can effectively increase the cross-linking density of the epoxy resin and reduce the surface energy of the epoxy resin coating, so that the contact area between the hydrophobic surface of the coating and the corrosive medium is reduced, which effectively prevents the adsorption of the corrosive medium and delays the time for it to enter the interior of the coating.

[0005] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:

[0006] One of the purposes of the present invention is to provide a method for preparing a waterborne epoxy resin modified with stearic acid / chitosan modified multi-walled carbon nanotubes, comprising the following steps:

[0007] S1, chitosan modified multi-walled carbon nanotubes and stearic acid undergo condensation reaction under the action of a coupling agent to obtain stearic acid / chitosan modified multi-walled carbon nanotubes;

[0008] S2, stearic acid / chitosan modified multi-walled carbon nanotubes undergo cross-linking reaction with water-based epoxy resin and water-based epoxy curing agent to obtain stearic acid / chitosan modified multi-walled carbon nanotubes modified water-based epoxy resin.

[0009] The second object of the present invention is to provide a stearic acid / chitosan modified multi-walled carbon nanotube modified waterborne epoxy resin prepared by the above-mentioned preparation method.

[0010] The third object of the present invention is to provide the use of the aforementioned stearic acid / chitosan modified multi-walled carbon nanotube modified waterborne epoxy resin in anti-corrosion coatings.

[0011] The beneficial effects of the present invention are:

[0012] (1) The chitosan used in the present invention is the only cationic polysaccharide among natural polysaccharides. It is non-toxic and has good film-forming properties. It has strong chelating ability with metals and can be used as an efficient green corrosion inhibitor. In addition, the use of chitosan to modify multi-walled carbon nanotubes can significantly improve the agglomeration phenomenon of multi-walled carbon nanotubes in the matrix.

[0013] (2) The stearic acid used in the present invention is a fatty acid containing a long carbon chain and low surface energy, which is widely used in preparing hydrophobic coatings. Introducing low surface energy materials on the metal surface to prepare a hydrophobic coating is also an effective method to enhance corrosion resistance to prevent corrosive ions from etching the metal.

[0014] (3) The stearic acid / chitosan modified multi-walled carbon nanotubes synthesized in the present invention can enhance the interfacial bonding strength between the multi-walled carbon nanotubes and the epoxy resin matrix, make the internal structure of the epoxy resin coating denser, reduce the formation of micropore defects, and effectively improve the shielding performance of the coating against corrosive electrolytes. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The figures are effect diagrams of salt spray aging experiments on coatings formed by curing the modified waterborne epoxy resins prepared in Examples 1-3 and Comparative Example 1, and the waterborne epoxy resin prepared in Comparative Example 2. DETAILED DESCRIPTION

[0016] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.

[0017] The present invention provides a method for preparing a waterborne epoxy resin modified by stearic acid / chitosan modified multi-walled carbon nanotubes, comprising the following steps:

[0018] S1, chitosan modified multi-walled carbon nanotubes and stearic acid undergo condensation reaction under the action of a coupling agent to obtain stearic acid / chitosan modified multi-walled carbon nanotubes;

[0019] S2, stearic acid / chitosan modified multi-walled carbon nanotubes undergo cross-linking reaction with water-based epoxy resin and water-based epoxy curing agent to obtain stearic acid / chitosan modified multi-walled carbon nanotubes modified water-based epoxy resin.

[0020] Furthermore, the coupling agent includes but is not limited to 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl). In the present invention, a water-soluble coupling agent is preferred.

[0021] Furthermore, the mass ratio of the chitosan-modified multi-walled carbon nanotubes to stearic acid and coupling agent is 1:1:(2-5).

[0022] Furthermore, the waterborne epoxy curing agent includes but is not limited to at least one of polyetheramine, ethylenediamine, and diethylenetriamine.

[0023] Furthermore, the mass ratio of the waterborne epoxy resin to the waterborne epoxy curing agent is 2:(0.5-1).

[0024] Furthermore, the amount of the stearic acid / chitosan modified multi-walled carbon nanotubes is 0.5-1.5% of the total mass of the epoxy resin and the water-based epoxy curing agent.

[0025] Furthermore, the chitosan-modified multi-walled carbon nanotubes are prepared by depositing chitosan on the surface of the multi-walled carbon nanotubes using a crosslinking agent.

[0026] Furthermore, the cross-linking agent includes but is not limited to at least one of glutaraldehyde and formaldehyde.

[0027] Furthermore, the usage ratio of chitosan, multi-walled carbon nanotubes and cross-linking agent is (2-5) g: 1 g: (3-8) mL.

[0028] The present invention uses glutaraldehyde and / or formaldehyde as a cross-linking agent, and uses electrostatic adsorption to adsorb chitosan on the surface of multi-walled carbon nanotubes to improve the dispersibility of multi-walled carbon nanotubes; then, stearic acid is grafted by a water-soluble coupling agent to synthesize multi-walled carbon nanotubes modified with stearic acid / chitosan, which are blended with water-based epoxy resin. Chitosan can be cross-linked with epoxy resin, thereby enhancing the interfacial bonding strength between multi-walled carbon nanotubes and epoxy resin matrix, and the cross-linked epoxy resin coating structure is more compact, reducing the formation of microporous defects; the grafting of stearic acid enhances the hydrophobicity of the coating, and effectively improves the shielding performance of the coating against corrosive electrolytes. In addition, the amino and hydroxyl groups on the side chains of the chitosan molecular structure have strong chemical activity, strong chelating ability with metals, and can be used as an efficient green corrosion inhibitor.

[0029] The invention provides a stearic acid / chitosan modified multi-walled carbon nanotube modified waterborne epoxy resin prepared by the above-mentioned preparation method.

[0030] The present invention provides the use of the aforementioned stearic acid / chitosan modified multi-walled carbon nanotube modified waterborne epoxy resin in anti-corrosion coatings.

[0031] Example 1

[0032] 1) Weigh 0.8 g of chitosan and dissolve it in 200 mL of dilute acetic acid solution, stir for 12 h to obtain a chitosan solution; weigh 0.2 g of multi-walled carbon nanotubes and disperse them in 20 mL of deionized water, and then slowly add them to the chitosan solution after ultrasonic treatment for 30 min, and the obtained mixed solution is stirred and reacted at 98° C. for 6 h; cool to room temperature, adjust the solution pH to 10 with dilute ammonia water, and then add 1 mL of glutaraldehyde, and stir and react at 60° C. for 3 h; after the reaction, wash and centrifuge with dilute acetic acid and deionized water, and freeze-dry to obtain chitosan-modified multi-walled carbon nanotubes.

[0033] 2) Weigh 0.2 g of chitosan-modified multi-walled carbon nanotubes and disperse them in 20 mL of deionized water, and ultrasonicate for 30 min to obtain a chitosan-modified multi-walled carbon nanotube solution; weigh 0.2 g of stearic acid and 0.67 g of EDC·HCl and dissolve them in a mixture of 28 mL of acetone and 12 mL of anhydrous ethanol, add them to the chitosan-modified multi-walled carbon nanotube solution, and stir and react at 60° C. for 24 h; after the reaction, wash with deionized water and ethanol, centrifuge, and dry at 60° C. to obtain stearic acid / chitosan-modified multi-walled carbon nanotubes.

[0034] 3) Weigh 0.03 g of stearic acid / chitosan modified multi-walled carbon nanotubes and disperse them in 1.5 mL of anhydrous ethanol, then mix them with 4 g of water-based epoxy resin E-51, add 2 g of polyetheramine (molecular weight 190.283) after ultrasonic treatment for 30 min, and stir for 20 min to obtain stearic acid / chitosan modified multi-walled carbon nanotube modified water-based epoxy resin (SCCNTs / EP1).

[0035] Example 2

[0036] The method of Example 1 was followed, except that in step 3), the amount of stearic acid / chitosan modified multi-walled carbon nanotubes was 0.06 g, and the amount of anhydrous ethanol was 3 mL, to obtain stearic acid / chitosan modified multi-walled carbon nanotubes modified waterborne epoxy resin (SCCNTs / EP2).

[0037] Example 3

[0038] The method of Example 1 was followed, except that in step 3), the amount of stearic acid / chitosan modified multi-walled carbon nanotubes was 0.09 g, and the amount of anhydrous ethanol was 4.5 mL, to obtain stearic acid / chitosan modified multi-walled carbon nanotubes modified waterborne epoxy resin (SCCNTs / EP3).

[0039] Example 4

[0040] The method of Example 2 was followed, except that the amount of EDC·HCl used in step 2) was 1 g, thereby obtaining a stearic acid / chitosan-modified multi-walled carbon nanotube-modified waterborne epoxy resin.

[0041] Example 5

[0042] The method of Example 2 is followed, except that the amount of polyetheramine used in step 3) is 1 g, thereby obtaining stearic acid / chitosan modified multi-walled carbon nanotube modified waterborne epoxy resin.

[0043] Example 6

[0044] The method of Example 2 was followed, except that in step 1), the amount of chitosan used was 1 g, and the amount of glutaraldehyde used was 1.6 mL, to obtain stearic acid / chitosan modified multi-walled carbon nanotube modified waterborne epoxy resin.

[0045] Comparative Example 1

[0046] The method of Example 2 is followed, except that step 2) is omitted, and stearic acid / chitosan modified multi-walled carbon nanotubes are directly replaced with chitosan modified multi-walled carbon nanotubes to obtain chitosan modified multi-walled carbon nanotube modified waterborne epoxy resin (CCNTs / EP).

[0047] Comparative Example 2

[0048] 4 g of waterborne epoxy resin E-51 was weighed and ultrasonically treated for 30 min, then 2 g of polyetheramine was added and stirred for 20 min to obtain a waterborne epoxy resin (EP).

[0049] The stearic acid / chitosan modified multi-walled carbon nanotube modified waterborne epoxy resin prepared in Examples 1-6, the chitosan modified multi-walled carbon nanotube modified waterborne epoxy resin prepared in Comparative Example 1, and the waterborne epoxy resin prepared in Comparative Example 2 were poured into a mold to form a coating, and cured in an oven at 70°C for 24 hours. The coating was tested for performance, and the test results are shown in Table 1.

[0050] Water absorption test:

[0051] A certain mass of coating film was immersed in ultrapure water for 24 hours, and its mass before and after immersion was weighed. The water absorption rate of the coating film was calculated according to formula (1):

[0052]

[0053] Wherein: Q represents the water absorption rate (%); M represents the mass of the coating sample after water absorption (g); m represents the mass of the coating sample before water absorption (g).

[0054] Contact angle test:

[0055] The water contact angle of the coating with a smooth surface was tested using a DSA10-MK2 contact angle meter. Each coating was tested three times and the middle value was taken.

[0056] Impact resistance test:

[0057] The impact test machine KX-DB-501 was used according to the standard GB / T 6739-1996.

[0058] Table 1

[0059] Test items Example 1 Example 2 Example 3 Example 4 Water absorption (%) 4.89 4.12 4.73 4.26 Contact angle (°) 98.3 104.3 102.8 103.9 Impact resistance (kg·cm) 40 45 45 45 Test items Example 5 Example 6 Comparative Example 1 Comparative Example 2 Water absorption (%) 4.35 3.98 5.84 11.23 Contact angle (°) 103.0 105.4 77.5 62.8 Impact resistance (kg·cm) 46 47 40 40

[0060] It can be seen from Table 1 that, compared with Comparative Examples 1 and 2, the coatings formed by curing the stearic acid / chitosan-modified multi-walled carbon nanotubes modified with water-based epoxy resin prepared in Examples 1-6 have good hydrophobicity and mechanical properties.

[0061] The stearic acid / chitosan modified multi-walled carbon nanotube modified water-based epoxy resin prepared in Examples 1-3, the chitosan modified multi-walled carbon nanotube modified water-based epoxy resin prepared in Comparative Example 1, and the water-based epoxy resin prepared in Comparative Example 2 were respectively coated on tinplate, and the coating thickness was controlled to be 100±2μm. The coating was cured in an oven at 70°C for 24h, and an "×" treatment was drawn on the surface of the coating. Then, the coating was placed in a salt spray test box for salt spray aging test. The temperature of the salt spray test box was 35±2°C, and 5wt% NaCl solution was used as the spray solution, and the spraying was continuous for 30d.

[0062] The test results show that after 10 days of salt spray test, a large number of corrosion products appeared around the scratches of the EP coating, and the coating was white and blistering; after 30 days of salt spray test, the rust marks of the EP coating spread to the entire coating surface, and the coating showed signs of falling off; the rust marks of the CCNTs / EP coating were greatly reduced compared with the EP coating, and the blistering phenomenon of the coating was significantly improved. Compared with the EP and CCNTs coatings, the SCCNTs / EP1~3 coatings showed slight rust marks at and around the scratches after 30 days of salt spray test, and the corrosion inhibition effect was significantly enhanced. Among them, the SCCNTs / EP2 coating had the least rust spots on the surface, which were mainly concentrated around the scratches. The coating surface was smooth and did not bubble, and it had the best barrier performance.

[0063] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a waterborne epoxy resin modified with stearic acid / chitosan-modified multi-walled carbon nanotubes, characterized in that: The steps include: S1, chitosan modified multi-walled carbon nanotubes and stearic acid undergo condensation reaction under the action of a coupling agent to obtain stearic acid / chitosan modified multi-walled carbon nanotubes; S2, stearic acid / chitosan modified multi-walled carbon nanotubes undergo cross-linking reaction with water-based epoxy resin and water-based epoxy curing agent to obtain stearic acid / chitosan modified multi-walled carbon nanotubes modified water-based epoxy resin.

2. The preparation method according to claim 1, characterized in that: The coupling agent is 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the chitosan modified multi-walled carbon nanotubes to stearic acid and coupling agent is 1:1:(2-5).

4. The preparation method according to claim 1, characterized in that: The waterborne epoxy curing agent is at least one of polyetheramine, ethylenediamine and diethylenetriamine.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the waterborne epoxy resin to the waterborne epoxy curing agent is 2:(0.5-1); the amount of the stearic acid / chitosan modified multi-walled carbon nanotubes is 0.5-1.5% of the total mass of the epoxy resin and the waterborne epoxy curing agent.

6. The preparation method according to claim 1, characterized in that: The chitosan-modified multi-walled carbon nanotubes are prepared by depositing chitosan on the surface of the multi-walled carbon nanotubes via a crosslinking agent.

7. The preparation method according to claim 6, characterized in that: The cross-linking agent is at least one of glutaraldehyde and formaldehyde.

8. The preparation method according to claim 6, characterized in that: The usage ratio of the chitosan, the multi-walled carbon nanotubes and the cross-linking agent is (2-5) g: 1 g: (3-8) mL.

9. Stearic acid / chitosan modified multi-walled carbon nanotube modified waterborne epoxy resin prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the stearic acid / chitosan modified multi-walled carbon nanotube modified waterborne epoxy resin according to claim 9 in anti-corrosion coatings.

Citation Information

Patent Citations

  • Aromatic aldehyde / chitosan non-covalent modified carbon nano-tube composite material

    CN106477557A

  • Chitosan-stearic acid composite oil absorption material with strong magnetism and high hydrophobicity

    CN110624519A

  • High-strength flexible fireproof cable

    CN113429648A

  • Corrosion-resistant composite material containing modified carbon nanotubes and preparation method of corrosion-resistant composite material

    CN114958146A

  • Anticorrosive composite coating on surface of steel structure as well as preparation method and application of anticorrosive composite coating

    CN116694186A

Cited By

  • Polymer composite material for circulating water pump and preparation method thereof

    CN121825371A